2005
DOI: 10.1634/theoncologist.10-5-306
|View full text |Cite
|
Sign up to set email alerts
|

The Issue of Renal Safety of Zoledronic Acid from a Nephrologist's Point of View

Abstract: In response to Body letter to the editor regarding "safety of intravenous and oral bisphosphonates and compliance with dosing regimens". Oncologist. 2005 May;10(5):318-9. (correspondence) Conte P, Guarneri V. In response to Jackson letter to the editor regarding safety of intravenous and oral bisphosphonates and compliance with dosing regimens". Oncologist. 2005 May;10(5):315-6. (correspondence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
(1 reference statement)
1
8
0
6
Order By: Relevance
“…17 The renal toxicity of the intravenous bisphosphonates used in patients with malignant diseases involving bone is probably enhanced by risk factors for kidney function which may be present in these patients: pre-existing Chronic Kidney Disease (CKD), multiple myeloma, hypercalcaemia, hypertension, diabetes mellitus, advanced age, chemotherapy or previous treatment with a bisphosphonate. 16,18 Important factors which may increase renal toxicity of the intravenous bisphosphonates are higher dose, shorter infusion times or dose interval lower than recommended. 16,19 The total dose of the drug which has been administered during a long-term treatment may also play a role because of its probable cumulative effect.…”
Section: Ocular Adverse Eventsmentioning
confidence: 99%
“…17 The renal toxicity of the intravenous bisphosphonates used in patients with malignant diseases involving bone is probably enhanced by risk factors for kidney function which may be present in these patients: pre-existing Chronic Kidney Disease (CKD), multiple myeloma, hypercalcaemia, hypertension, diabetes mellitus, advanced age, chemotherapy or previous treatment with a bisphosphonate. 16,18 Important factors which may increase renal toxicity of the intravenous bisphosphonates are higher dose, shorter infusion times or dose interval lower than recommended. 16,19 The total dose of the drug which has been administered during a long-term treatment may also play a role because of its probable cumulative effect.…”
Section: Ocular Adverse Eventsmentioning
confidence: 99%
“…Important factors which may increase renal toxicity of the intravenous bisphosphonates are higher dose, shorter infusion times (< 15 ml/minute) or dose interval lower than recommended [15,23,24]. The total dose of the drug which has been administered during a long-term treatment may also play a role because of its probable cumulative effect [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant side-effect, although considered rare, associated with the use of zoledronic acid is renal toxicity [16Á18]. Nephrotoxicity is potentially life-threatening [19,20]. In the USA, Chang et al [21] highlighted 72 cases in which clinicians reported renal failure associated with zoledronic acid therapy to the Food and Drug Administration; 27 patients required dialysis, and 18 died.…”
mentioning
confidence: 99%